1994
DOI: 10.1007/bf00014596
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of gene expression

Abstract: Although feedback regulation of photosynthesis by carbon metabolites has long been recognized and investigated, its underlying molecular mechanisms remain unclear. The recent discovery that glucose and acetate trigger global repression of maize photosynthetic gene transcription provides the first direct evidence that a fundamental mechanism is used for feedback regulation of photosynthesis in higher plants. The metabolic repression of photosynthetic genes has now been found in many higher plants and is likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
247
2
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(260 citation statements)
references
References 108 publications
9
247
2
2
Order By: Relevance
“…Krapp et al, 1993;Sheen, 1994; have proposed that the increased metabolism of accumulated soluble sugars at high CO 2 may trigger a repression of photosynthetic gene transcription. This repression is thought to be mediated by hexose metabolism via cytosolic hexokinase (Jang and Sheen, 1994;Jang et al, 1997), but we have limited knowledge of the suggested biochemical role of hexokinase as a sugar sensor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krapp et al, 1993;Sheen, 1994; have proposed that the increased metabolism of accumulated soluble sugars at high CO 2 may trigger a repression of photosynthetic gene transcription. This repression is thought to be mediated by hexose metabolism via cytosolic hexokinase (Jang and Sheen, 1994;Jang et al, 1997), but we have limited knowledge of the suggested biochemical role of hexokinase as a sugar sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Sugars are known to influence many metabolic and cellular processes in both prokaryotes and eukaryotes, in part through modulation of gene expression (for reviews, see Sheen, 1994;Saier et al, 1995;Koch, 1996). To date, there is substantial evidence indicating that increased sugar levels can trigger repression of photosynthetic gene transcription.…”
mentioning
confidence: 99%
“…27,28 In sut1-m1 mutants, photosynthetic and stomatal conductance rates are comparable to wild-type plants only in leaves emerging from the whorl (leaf 7 in Fig. 1E and F), which are in the process of transitioning to source tissue.…”
Section: Accumulation Of Carbohydrates In Sut1 Mutant Leaves Is Assocmentioning
confidence: 93%
“…*Current address: Department of Molecular Genetics, John Innes Centre, Norwich Research Park, Colney, Norwich NR4 7UH, UK. plant (for review see Sheen, 1994;Stitt, 1991). In particular, photosynthesis is inhibited when the production of photosynthates exceeds the rate of utilization by sinks, a sink being an organ which utilizes or stores carbohydrate generated by other parts of the plant.…”
Section: Introductionmentioning
confidence: 99%